2014
DOI: 10.1051/0004-6361/201423570
|View full text |Cite
|
Sign up to set email alerts
|

Mass loss from inhomogeneous hot star winds

Abstract: Aims. We provide a fast and easy-to-use formalism for treating the reduction in effective opacity associated with optically thick clumps in an accelerating two-component medium. Methods. We develop and benchmark effective-opacity laws for continuum and line radiative transfer that bridge the limits of optically thin and thick clumps. We then use this formalism to i) design a simple method for modeling and analyzing UV wind resonance lines in hot, massive stars, and ii) derive simple correction factors to the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 46 publications
9
104
0
1
Order By: Relevance
“…For the strong-wind Muijres et al (2012) showed that wind solutions based on a detailed treatment of the line force yielded mass-loss rates to within 0.1 dex when adopting the same terminal flow velocities, supporting the reliability of the global energy conservation assumption applied by Vink et al (2001). If the material in the outflow would be concentrated in relatively few and strongly over-dense clumps, porosity effects may cause photons to escape 'in-between the clumps' reducing the linedriving force and hence the mass-loss rate (for corresponding scaling relations, see Sundqvist et al 2014). However, Muijres et al (2011) demonstrated that for clumps that are smaller than 1/100th of the local density scale height, thought to represent physically realistic situations, such effects are not significant for volume-filling factors as low as approximately 1/30.…”
Section: Mass Loss and Modified Wind Momentummentioning
confidence: 61%
“…For the strong-wind Muijres et al (2012) showed that wind solutions based on a detailed treatment of the line force yielded mass-loss rates to within 0.1 dex when adopting the same terminal flow velocities, supporting the reliability of the global energy conservation assumption applied by Vink et al (2001). If the material in the outflow would be concentrated in relatively few and strongly over-dense clumps, porosity effects may cause photons to escape 'in-between the clumps' reducing the linedriving force and hence the mass-loss rate (for corresponding scaling relations, see Sundqvist et al 2014). However, Muijres et al (2011) demonstrated that for clumps that are smaller than 1/100th of the local density scale height, thought to represent physically realistic situations, such effects are not significant for volume-filling factors as low as approximately 1/30.…”
Section: Mass Loss and Modified Wind Momentummentioning
confidence: 61%
“…By assuming that the non-uniformity of the outflow is caused by a statistical ensemble of small-scale density inhomogeneities or clumps, we are able to use a so-called porosity formalism (Owocki et al 2004;Owocki & Cohen 2006;Sundqvist et al 2012Sundqvist et al , 2014 to describe the effect of a clumpy outflow on its chemistry. See also Feldmeier et al (2003) and Oskinova et al (2004Oskinova et al ( , 2006 for an alternative formulation regarding radiative transfer effects in an inhomogeneous medium.…”
Section: Porosity Formalismmentioning
confidence: 99%
“…For ease of notation, we drop the radial dependency of all expressions. The density contrast between the inter-clump component and the mean density is set by the parameter (Sundqvist et al 2014)…”
Section: Porosity Formalismmentioning
confidence: 99%
“…However, even for extinction processes that scale linearly with density, e.g. electron scattering or bound-free absorption, the effective opacity can be reduced by the medium's "porosity", associated with the enhanced radiation transport through relatively lowdensity regions (Shaviv 1998;Owocki et al 2004;Oskinova et al 2004Oskinova et al , 2007Sundqvist et al 2014).…”
Section: Introductionmentioning
confidence: 99%